Pemilihan Supplier Kedelai dengan Metode AHP Dan TOPSIS (Studi Kasus UKM Tahu Pak Wit Di Desa Ledok Kulon, Bojonegoro) - Indriartiningtias, Retno; Trisita Novianti; Zuhriyah, Anifatuz (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2024)
Raw materials as the most important factors in production activities, are obtained from suppliers. Suppliers are partners who ensure the availability of raw materials for the continuity of the company's production. Therefore, it is necessary for companies to choose the right supplier. The problem that occurs in Pak Wit's Tofu SME is that SMEs often change suppliers in procuring soybean raw materials because the SMEs do not have a fixed soybean supplier. This fact results in no certainty of raw materials from the supplier so that SMEs often experience a shortage of quality raw materials. This study aims to select the best supplier according to the criteria set by SMEs. There are 4 suppliers who are candidates with 4 criterias (price, quality, service and flexibility in delivery) used in choosing the best supplier. This research uses AHP to weight the criteria and TOPSIS to rank suppliers. The results of calculations with AHP found that the quality criteria were the first priority, with a value of 0.58. While with the TOPSIS method it was found that supplier 2 was the selected supplier with the highest preference of 0.941.